Sarcopenia and surgical outcomes in patients undergoing oncologic colonic surgery. (28th May 2021) - Schneider, M; Hübner, M; Becce, F; Koerfer, J; Collinot, J -A; Demartines, N; Hahnloser, D; Grass, F; Martin, D
Abstract: Objective: Sarcopenia is a marker for malnutrition and frailty which could lead to higher complication rate and prolonged length of stay (LOS) after surgery. The study aim was to assess the correlation between sarcopenia and clinical outcomes in oncologic colonic surgery. Methods: This retrospective study included consecutive patients operated between 2014 and 2019. Three radiological indices of sarcopenia were measured at the level of the third lumbar vertebra on preoperative CT scans: Skeletal Muscle Area (SMA), Skeletal Muscle Radiation Attenuation (SMRA), and Skeletal Muscle Index (SMI). Patients with major complications (> grade 3a) according to Clavien classification were compared to those without. Statistical correlation between sarcopenia indices, LOS and Comprehensive Complication Index (CCI) was tested by use of the Pearson correlation. Results: A total of 325 patients were included, 50 (15.4%) with and 275 (84.6%) without major complications. SMA and SMI were comparable between both groups (respectively 126.0 vs 125.2 cm2, p = 0.974, and 43.4 vs 44.3 cm2/m2, p = 0.636), while SMRA was significantly lower in patients with major complications (33.6 vs 37.3 HU, p = 0.018). A lower SMRA was correlated with prolonged LOS (r=-0.207, p < 0.01) and higher CCI (r=-0.144, p < 0.01), while the other sarcopenia indices had no influence on surgical outcomes. Conclusion: Preoperative SMRA or muscle quality appears to be a weak predictor for adverse outcomes after oncologic colectomy.